Biotrickling filter for the removal of volatile sulfur compounds from sewers: A review. (August 2021) - Bu, Hao; Carvalho, Gilda; Yuan, Zhiguo; Bond, Philip; Jiang, Guangming
Abstract: Volatile sulfur compounds (VSCs) were identified as the dominant priority odorants emitted from sewers, including hydrogen sulfide (H2 S), methyl mercaptan (MM), dimethyl disulfide (DMDS) and dimethyl sulfide (DMS). Biotrickling filter (BTF) is a widely-applied technology for odour abatement in sewers because of its relatively low operating cost and efficient H2 S removal. The authors review the mechanisms and performance of BTF for the removal of these four VSCs, and discuss the key influencing factors including of empty bed residence time (EBRT), pH, temperature, nutrients, water content, trickling operation and packing materials. Besides, measures to improve the VSCs removal in BTF are proposed in the context of key influencing factors. Finally, the review assesses the new challenges of BTF for sewer emissions treatment, namely with respect to the performance of BTF for greenhouse gases (GHG) treatment. Graphical abstract: Image 1 Highlights: The rate-limiting step of VOSCs' removal in BTF was deduced. The key influence factors to VSCs removal in BTF were discussed. Strategies for improving VOSCs' removal in BTF were proposed. The challenges in the BTF development for sewer emissions treatment were evaluated.